The Combination of Ultraviolet-B and Vitamin K2 Exposure Effect on Fibroblast-like cell Number in Wistar Rats - Nelwan, Sindy Cornelia; Tedjosasongko, Udijanto; Dharmawan, Devi; Leo, Leviena Merlynike; Ardiana, Hana Ai; Rahmawati, Siti (Indonesian Journal of Dental Medicine, 2023)
Background: Vitamin D deficiency in children is one of the problems most often discussed and received attention from around the world today, especially during the Corona virus disease-19 (Covid-19) pandemic. Vitamin D3 increases the production of vitamin K2 protein and activates a protein involved in bone metabolism. Vitamin K2 increases bone formation by stimulating osteoblast differentiation, regulating mineralization of the extracellular matrix, regulating bone marker gene expression, and inhibiting osteoclastogenesis. Purpose: to analyzed the effect of sun exposure, Ultraviolet-B (UV-B) and vitamin K2 supplementation on fibroblast-like cell as bone formation marker in Wistar rats (Rattus novergicus). Methods: twenty-four samples divided into 4 groups namely control group, UV-B group, vitamin K2 group, combination of UV-B and vitamin K2 group. After 21 days, extraction of lower incisors was done to examine fibroblast-like cell number "‹"‹after treatment. After being decalcified, specimens underwent histological evaluation using Haemotoxylin and Eosin staining to observe the fibroblast-like cell number. Result: Data analysis of fibroblast like cells number expression using one way analysis of variance (ANOVA) test showed a significant difference between sample groups (p<0.05). Conclusion: The combination of UV-B exposure and vitamin K2 administration group increased of fibroblast-like cells in Wistar rats (R. novergicus).